Evaluation of various permanent magnet arrangements on linear actuator. - Abdul Shukur, Fairul Azhar; Misron, Norhisam; Wakiwaka, Hiroyuki; Kunihisa, Tashiro; Nirei, Masami (2012)
Linear actuator are used to provide linear motion in the absence of a motion translator, By using the linear actuator, the linear motion can be produce with high degree of efficiency. Linear actuators can be designed with and without slots; moreover, there are various types of magnetization arrangements can be applied to the mover. In this paper, ten different magnetization arrangements were used to evaluate .slot and slot-less linear actuator. Nine different performance characteristics were used to find the best structure of linear actuator. Results s~ow that, the slot-less types of linear actuators generally have a better dynamic performance, while the slot types of linear actuators have a better static performance. Four different structures with different magnetization arrangements were selected as the best models of linear actuators.